PENGARUH PERCEIVED SUPERVISOR SUPPORT, PERCEIVED COWORKER SUPPORT DAN PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP STRES KERJA KARYAWAN PT MANDIRI JOGJA INTERNASIONAL - Fahri Rizki Saputro; Ignatius Soni Kurniawan; Nala Tri Kusuma (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
This study aims to determine the effect of perceived supervisor support, perceived coworker support, and perceived organizational support on job stress of employees of PT Mandiri Jogja Internasional. This study uses quantitative research methods and primary data in this study were taken using a questionnaire obtained by census on 68 respondents. In obtaining this research sample using classical assumption test tools and multiple linear regression analysis. The tests in the classical assumption test include normality test, muticolonierity test, and heteroscedasticity test while the multiple regression test includes the t-test. The results of this study indicate that perceived supervisor support has a negative and significant effect on employee work stress. There is a positive and significant influence of the perceived coworker support variable on employee work stress. Likewise, there is also a negative and significant effect of the variable perceived organizational support on employee work stress.